The relationship of urban agglomeration to income and poverty in the Philippines - Javier, Jose Antonio P.; Magno, Cielo D. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
A key assumption behind regional growth strategies is that agglomeration carries economic benefits. The study investigates whether agglomeration, particularly of the dominant services sector, is linked to benefits _ higher income and lower poverty. Agglomeration measures, obtained by computing spatial Gini coefficients and location quotients, are analyzed using OLS regression for regions in the Philippines in 2012 and 2015. Analysis reveals that agglomeration of services, particularly of the high_skilled sector, is linked to high income but is also associated with more poverty. The latter relationship is attributed to two factors_ (1) congestion in the city as a result of urban_rural migration and (2) exclusivity of the services sector to the more educated and affluent workers. To mitigate the poverty associated with high agglomeration, adequate infrastructure and social services for the urban poor must be in place, along with incentives that improve the poor_s access to higher skills and educational levels.
Thesis (Master in Development Economics) -- University of the Philippines Diliman
Keywords: Industrial clusters -- Philippines; Income -- Philippines; Poverty -- Philippines